Factor VIII Ise (R2159C) in a Patient with Mild Hemophilia A, an Abnormal Factor VIII with Retention of Function but Modification of C2 Epitopes - Suzuki, Hiroshi; Shima, Midori; Arai, Morio; Kagawa, Kazuhiko; Fukutake, Katuyuki; Kamisue, Seiki; Nakai, Hiroaki; Morichika, Shogo; Tanaka, Ichiro; Inoue, Masakazu; Gale, koren; Tuddenham, Edward G D; Yoshioka, Akira (Thrombosis and Haemostasis, 1997)
We found a patient with mild hemophilia A who had no detectable factor VIII antigen (FVIII:Ag), as shown by two-site ELISA using inhibitor alloantibodies (TK). We then analyzed A2, A2/B, and C2 antigen of the patient's DDAVP-induced FVIII using several anti-FVIII monoclonal antibodies. Factor VIII activity (FVIII : C) was increased from 12 to 42 Uldl by the administration of DDAVP. The DDAVPinduced increases in the A2 and A2/B antigens were 40 and 36 Uldl, respectively. However, the increase in the C2 antigen was only 7.5 Uldl. SSCP analysis and subsequent sequencing demonstrated an Arg to Cys transition at codon 2159. The anti-FVII1:C titer of monoclonal antibody, NMC-VIII15 which recognized the C2 domain, against normal plasma was 450 Bethesda Ulmg of IgG. However, the titer against DDAVP-treated patient's plasma was only 15 Bethesda Ulmg. We also tested DDAVP-induced increase in the FVIII : Ag in another mild hemophilia A patient with the same mutation at Arg2159. Increase in his C2 antigen levels was only 19% of those in the A2 and A2/B antigen. We designate this abnormal FVIII as FVIII Ise. Our results show that a missense mutation at Arg2159 to Cys modifies the antigenicity of the C2 domain.